2002
DOI: 10.3390/i3111188
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Energy Analysis of Nonclassical Antifolates with Pneumocystis carinii Dihydrofolate Reductase

Abstract: The x-ray structure of the Pneumocystis carinii dihydrofolate reductase (DHFR):trimethoprim:NADPH ternary complex obtained from the Protein Databank was used as a structural template to generate models for the following complexes: P. carinii DHFR:piritrexim:NADPH, P. carinii DHFR:epiroprim:NADPH, and P. carinii DHFR:trimetrexate:NADPH. Each of these complexes, including the original trimethoprim complex was then modeled in 60 angstrom cubes of explicit water and minimized to a rms gradient between 1.0 to 3.0 x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…The D-luciferin substrate for P. pyralis luciferase and TMP-SMX are amphipathic molecules (i.e., hydrophilic and hydrophobic areas are present within the same molecule) (19,32). The D-luciferin substrate and SMX-TMP antibiotic must permeate the outer membrane on the way into the periplasmic space and the cell, which means that that the outer membrane has special sieving properties.…”
Section: Discussionmentioning
confidence: 99%
“…The D-luciferin substrate for P. pyralis luciferase and TMP-SMX are amphipathic molecules (i.e., hydrophilic and hydrophobic areas are present within the same molecule) (19,32). The D-luciferin substrate and SMX-TMP antibiotic must permeate the outer membrane on the way into the periplasmic space and the cell, which means that that the outer membrane has special sieving properties.…”
Section: Discussionmentioning
confidence: 99%
“…In the first step, seven new compounds were synthesized and then they were evaluated for their inhibitory activities against human DHFR. These results were added to thirteen compounds reported by Gangjee et al (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13) [16], two compounds reported in our earlier work (14a and 15a) [5] and two new compounds (14e and 15f) recently reported in reference [17] in order to have a more complete and representative number of compounds (25 molecules in the complete series ( Figure 1 and Table 1)). In the next step, we performed MD simulations, QM calculations (using different levels of theory) and QTAIM analysis with the aim to obtain a correlation which allows the discrimination between compounds possessing similar affinities by the enzyme.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Dihydrofolate reductase (DHFR) is an excellent molecular target for this study because it has been and is currently studied by using different molecular modeling techniques [6][7][8][9]. Kerrigan et al have reported an interesting review about recent progress in molecular dynamics simulations of DHFR [10] and they conclude that "molecular mechanics calculations can work well to model the initial binding step of an inhibitor or substrate with…”
Section: Introductionmentioning
confidence: 99%